Eitan eats the world - Bernath, Eitan, 2002- (Clarkson Potter/Publishers, 2022)
A debut cookbook from a social media star Eitan Bernath presents eighty-five unique, illustrated recipes from fresh takes on comfort food classics like PB & J pancakes and double grilled cheese with blueberry-thyme jam to world dishes including green shakshuka and beef souvlaki.